MODEL PEMBELAJARAN SENTRA BALOK MODIFIKASI TERHADAP KEMAMPUAN KOGNITIF MEMAHAMI KONSEP UKURAN PADA ANAK AUTIS DI TK - MARATUS S, GUSTIN (Jurnal Pendidikan Khusus, 2016)
ABSTRACT This research was formed background by the importance of developing cognitive ability to understand the measurement concept to early age autism children. The ability of understanding measurement concept, one of them was big-small measurement belonged to autism children in TK Mentari School Sidoarjo still needed to be developed. It appeared to the ability of differentiating things based on big-small measurement, classifying things based on big-small measurement and sequencing things from big to small measurement. Through learning model of beam central modification, autism children were actively stimulated to do studying while playing activity and it gave freedom to the children to play freely on beam central modification. This purpose had purpose to prove the influence of learning model of beam central modification toward cognitive ability to understand the measurement concept to autism children in TK Mentari School Sidoarjo. This research used quantitative approach, with pre-experimental kind, and one group pretest – posttest design. The samples of this research were all autism children of group A in TK Mentari School Sidoarjo numbering 7 children whose ability in understanding the measurement concept still needed to be developed. The technique of data collection was collected using observation and documentation. The technique of data analysis applied statistic non parametric with Wilcoxon match pairs test. The research result indicated that there was enhancement value of cognitive ability to understand the measurement concept in initial observation or pretest was 49,73 becoming 74,07 in final observation or posttest. In addition, the research result also indicated Tcounted = 0 was smaller than Ttable = 2 with significant level 5%. If Tcounted < Ttable (0 < 2) it indicated that there was influence of learning model of beam central modification toward cognitive ability to understand the measurement concept to autism children in TK Mentari School Sidoarjo.     Keywords: Beam central modification, measurement concept